"I am not simply learning and regurgitating information, I am also learning about myself": learning portfolio practice and online distance students. Issue 1 (2nd January 2019) - Farrell, Orna; Seery, Aidan
ABSTRACT: This case study explored the experience of learning portfolio practice and whether learning portfolio practice facilitated the development of critical thinking skills among online distance students. Data were generated using the participant learning portfolio entries and two-time semi-structured interviews. Five themes were constructed in the data-led thematic analysis: being an online distance student, the experience of learning with a learning portfolio, my approach to learning, thinking critically in my learning portfolio, the sociology discipline context. Findings indicate that learning portfolio practice can enhance the nature of the learning experience by providing students with a personal space to evaluate their own learning, to process their thoughts and experience and to document their lives and learning in an authentic and meaningful way. The findings suggest that learning portfolio practice can facilitate the development of critical thinking skills within a disciplinary context.